Engaging with patients with diabetes: the role of social media in low-income healthcare organisations - Jose Rodriguez; Shabbir Syed-Abdul; Andrea Cano; Mohy Uddin; Fernanda Caceres (BMJ Health & Care Informatics)
Background Type 2 diabetes is the fastest-growing global health concern, and its global prevalence is projected to affect 643 million individuals by 2030. Social media platforms, like Facebook, have become crucial channels for healthcare organisations to engage with the public to promote prevention and disease management, especially in low-resource settings like Honduras. This study aims to perform a retrospective analysis of Honduran healthcare organisations’ Facebook posts to understand how effectively they engage diabetes-related content with their followers.Methods The top 10 followed healthcare organisations’ Facebook pages were taken as a sample. Data were retrieved from October 2023 to March 2024. Diabetic-related posts were identified using keywords and categorised based on their contents and features.Results Findings reveal significant disparities in the frequencies of posts and public engagement among different types of organisations. The majority of posts were classified under the miscellaneous category and text+image feature. Recipes and food-related posts were liked and shared the most among the followers.Conclusion The results of the study found that patients’ engagement with diabetes-related content was low in social media. The gap between patients’ participation and engagement highlights the need for reassessment and refinement of social media communication strategies for healthcare organisations to empower patients with diabetes through social media and increase public engagement.